Pengaruh Unggahan Promosi Pada Akun Instagram @almondcrispy.id Terhadap Keputusan Pembelian - Rafinda Janari; Reddy Anggara; Oky Oxygentry (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
The advancement of information technology has driven significant changes in marketing strategies, particularly through social media platforms like Instagram. This study aims to evaluate the impact of promotional content posts on the Instagram account @almondcrispy.id on consumer purchasing decisions. The research focuses on three key variables: intensity, message content, and attractiveness. Data were collected through a survey involving 90 respondents who follow the account. The results of regression testing show that all three variables significantly influence purchasing decisions, with a total contribution of 34.9%. The significance values for intensity are 0.048, message content 0.009, and attractiveness 0.015, all of which are below 0.05, indicating a strong influence. These findings demonstrate that structured visual promotions can effectively influence consumer purchasing decisions. The study adopts a theory which states that media exposure has a real impact on audience behavior. These findings can serve as a reference for designing digital marketing strategies, particularly for local SMEs.